The Influence of Organizational Culture and Teacher Competence on Teacher Performance through Teacher Job Satisfaction - Syihabudin Syihabudin; Uli Wildan Nuryanto; Yolla Sukma Handayani (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
The purpose of this study was to determine the direct effect of organizational culture and teacher competence on job satisfaction; the direct effect of organizational culture on performance, teacher competence and job satisfaction on performance; the indirect effect of organizational culture and teacher competence on performance through job satisfaction of Elementary School Teachers in Carenang District, Serang Regency, Banten Province. This study uses a quantitative method with a correlational approach. The population of this study was all Elementary School Teachers in Carenang District, Serang Regency, Banten Province, totaling 182 people. The sampling technique used was proportional random sampling. The sample size was 165 respondents. The research instrument was developed based on the grid compiled from the theory that has been explained in the theoretical basis. Data were collected using a questionnaire. The study was conducted in June-July 2024. The findings of this study indicate that organizational culture and teacher competence has a positive and significant effect on job satisfaction; organizational culture; teacher competence; and job satisfaction has a positive and significant effect on Performance; job satisfaction is able to mediate the influence of organizational culture and teacher competence on the Performance of Elementary School Teachers in Carenang District, Serang Regency, Banten Province